Effect of Financial Literacy, Financial Confidence, External Locus of Control, On Personal Finance Management (Object of Study on East Java Students) - Wijayanti, Nur; Kartawinata, Budi Rustandi (Budapest International Research and Critics University, 2022)
The level of consumption in the younger generation, including students, is increasing, influenced by the existence of social media. This happens because of the lack of student knowledge of financial management properly. For this reason, students must improve financial literacy and self-confidence both from themselves and factors that cannot be controlled by themselves in personal financial management. Data from the pre-survey results show that personal financial management and financial literacy are on average good, while the external financial locus of control variable tends to be low. This study aims to determine the effect of financial literacy, financial confidence, and external locus of control on personal finance management (object of study on students in East Java). The population in this study were students who were taking higher education educators in East Java. The sample used in this research is 400 respondents from East Java students. The method in this study was a questionnaire distributed randomly in various cities or districts in East Java. From the results of the analysis using SPSS 25. Methods of data analysis using descriptive and quantitative methods with Multiple Linear Regression analysis. The t-test was used to test the hypothesis partially, while the F-test was used to test the hypothesis simultaneously. Based on the results of the study, there is a significant influence between financial literacy, financial confidence, and external locus of control on personal finance management.